2017
DOI: 10.3934/publichealth.2017.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Related Stigma among College Students in the Midwest

Abstract: In general, U.S. college students have low perceived susceptibility of acquiring HIV infection while 15–25 percent of youth have had negative perceptions towards HIV positive individuals. Factors associated with HIV stigma among college students were examined in a convenience sample of 200 students. Descriptive and inferential statistics were utilized to summarize the data. Only four percent of participants responded correctly to HIV transmission knowledge items. HIV transmission knowledge scores were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
6
21
2
4
Order By: Relevance
“…41,43,44 However, as previous studies have demonstrated mixed findings regarding sex differences in HIV stigma, future studies with more rigorous designs are needed. 6,45 Moreover, Hong Kong students showed lower levels of the better-off-dead belief than Guangzhou students, which is consistent with previous findings, although both mainland Chinese and Hong Kong participants reported stronger stigma than American participants. 7 There is evidence for an association between collectivistic values and stigmatization.…”
Section: Discussionsupporting
confidence: 90%
“…41,43,44 However, as previous studies have demonstrated mixed findings regarding sex differences in HIV stigma, future studies with more rigorous designs are needed. 6,45 Moreover, Hong Kong students showed lower levels of the better-off-dead belief than Guangzhou students, which is consistent with previous findings, although both mainland Chinese and Hong Kong participants reported stronger stigma than American participants. 7 There is evidence for an association between collectivistic values and stigmatization.…”
Section: Discussionsupporting
confidence: 90%
“…Research conducted by Agus, Niken which states that students have a stigma against PLWHA and it was known that there is an influence of information exposure to stigma besides students who are not exposed to information related to HIV/AIDS risk of 2.21 times greater for stigma against PLWHA [16]. Research conducted by Alawad M et al, Tang W et al and Kingori C et al shows a significant relationship between health students' knowledge of the stigma given to PLWHA [17][18][19]. The health student's knowledge of HIV/AIDS will greatly influence how the individual will behave towards people with HIV or AIDS sufferers.…”
Section:  Issn: 2089-9823mentioning
confidence: 99%
“…However, SHK can be rather variable even for a relatively well-known disease like HIV/AIDS as is in uenced by several factors. A recent survey on 200 university students from the Mid-Western part of the USA reported adequate knowledge about HIV transmissibility in only 4% of them [56]. The authors of the latter study supposed an inversed relationship between SHK and stigma toward HIV/AIDS affected individuals [56].…”
Section: Discussionmentioning
confidence: 97%